Aqueous phase reforming coupled to catalytic wet air oxidation for the removal and valorisation of phenolic compounds in wastewater. (15th November 2020) - Oliveira, A.S.; Baeza, J.A.; Saenz de Miera, B.; Calvo, L.; Rodriguez, J.J.; Gilarranz, M.A.
Abstract: Aqueous phase reforming (APR) coupled to catalytic wet air oxidation (CWAO) has been investigated as an approach to remove phenolic compounds from wastewater, converting them into valuable gases. Partial oxidation of phenol was achieved in the first CWAO stage trying to minimize mineralization so to allow a high yield to valuable gases in the second APR stage. APR runs were carried out with different mixtures of compounds corresponding to phenol oxidation pathway (phenol, quinones, long and short chain acids) and representing different degrees of oxidation in CWAO stage. A range of TOC and COD removal (74–90%) was observed in APR stage for the single compounds, with higher removal for long chain acids. Likewise, long chain acids provided with the highest conversion to gases. APR of mixtures rich in acids gave the highest yield to CH4 (11.0 mmol CH4 /g TOCinitial ). H2 production was low in all cases, due to competing direct conversion of long and short chain acids into CH4 . TOC and COD removal from wastewater was similar in APR-CWAO and APR, however the conversion to gases and the yield to CH4 were markedly higher for APR-CWAO, thus overcoming the difficulties previously observed in the direct APR of phenol. Graphical abstract: Image 1 Highlights: APR-CWAO coupling to remove and valorise phenolic compounds-bearing wastewater. APR-CWAO resulted in a similar TOC and COD removal than direct APR. Methane and hydrogen are the main components in the gas produced by APR-CWAO. Conversion to gases and methane yield are higher in APR-CWAO than in APR.